Work ethic of clove farmers in development Economy in lacinde village, pitumpanua district Wajo district - St. Junaeda; novita, dian (Kampret Journal, 2024)
This research aims to find out (1) What is the work ethic of clove farmers in Lacinde Village, Pitumpanua District, Wajo Regency (2) What factors influence the work ethic of clove farmers in Lacinde Village, Pitumpanua District, Wajo Regency (3) What are the efforts of clove farmers in economic development in Lacinde Village, Pitumpanua District, Wajo Regency. This type of research is descriptive research that uses qualitative data. Data was collected by conducting observations, interviews with informants, documents obtained from related agencies and several photo documentations taken by researchers in the field. The research results show: (1) The work ethic of clove farmers in Lacinde Village is still lacking because clove farmers in Lacinde Village have low enthusiasm in carrying out their activities as farmers. (2) Factors that influence the work ethic of clove farmers are educational factors, community culture, and geographical environmental conditions. (3) Clove farmers' efforts to develop the family economy are to improve the quality of clove plants so that they can produce good fruit and thus get a high selling price. Clove farmers will also harvest cloves when the clove fruit is ready to be harvested. Clove farmers in Lacinde Village try to maintain the quality of cloves to be sold by only picking cloves when the cloves are ripe or have started to turn red, so that when they are dried the water content is minimal, because when the cloves have flowered they are only harvested, resulting in scales when dry. becomes reduced